Therapeutic hypothermia promotes cerebral blood flow recovery and brain homeostasis after resuscitation from cardiac arrest in a rat model. Issue 10 (October 2019) - Wang, Qihong; Miao, Peng; Modi, Hiren R; Garikapati, Sahithi; Koehler, Raymond C; Thakor, Nitish V
Laboratory and clinical studies have demonstrated that therapeutic hypothermia (TH), when applied as soon as possible after resuscitation from cardiac arrest (CA), results in better neurological outcome. This study tested the hypothesis that TH would promote cerebral blood flow (CBF) restoration and its maintenance after return of spontaneous circulation (ROSC) from CA. Twelve Wistar rats resuscitated from 7-min asphyxial CA were randomized into two groups: hypothermia group (7 H, n  = 6), treated with mild TH (33–34℃) immediately after ROSC and normothermia group (7 N, n  = 6, 37.0 ± 0.5℃). Multiple parameters including mean arterial pressure, CBF, electroencephalogram (EEG) were recorded. The neurological outcomes were evaluated using electrophysiological (information quantity, IQ, of EEG) methods and a comprehensive behavior examination (neurological deficit score, NDS). TH consistently promoted better CBF restoration approaching the baseline levels in the 7 H group as compared with the 7 N group. CBF during the first 5–30 min post ROSC of the two groups was 7 H:90.5% ± 3.4% versus 7 N:76.7% ± 3.5% ( P  < 0.01). Subjects in the 7 H group showed significantly better IQ scores after ROSC and better NDS scores at 4 and 24 h. Early application of TH facilitates restoration of CBF back to baseline levels after CA, which in turn results in the restoration of brain electrical activity and improved neurological outcome.